Sertipikasi Massal Swadaya (Sms) Sebagai Usaha Mempercepat Pensertipikatan Tanah Dan Menciptakan Tata Tertib Pertanahan Di Desa Lebosari Kecamatan Kangkung Kabupaten Kendal - Eko Rizky Pribadi, Hj. Endang Sri Santi, Henny Juliani (Diponegoro Law Journal, 2012)
This thesis is titled "Governmental certificate Bulk (SMS) For Accelerating Business Pensertipikatan Creating Code Land And Land In Rural District Lebosari Kangkung Kendal". Given the importance of soil for human life, naturally the regulation of land is set in such a way, so as to minimize the problems in the field of land and land to create order. One important thing to realize orderly in land is the legal certainty of land title deed by way of creation. Making land certificate aims to provide legal protection to the certificate holder. As per article 19 paragraph 1 of the BAL, the registration certificate is to realize "Chess Rules of Land" that is orderly land law, land administration order, orderly use of land, and the orderly maintenance of the land and the environment. Bulk certificate Governmental Studies (SMS) as an attempt to speed up land and creating persertifikatan order of land in the Village District Lebosari Kangkung Kendal aims to determine the implementation of Governmental certificate Bulk (SMS), especially in the publishing sertipikatnya know the procedure, the role of the head of the village, as well as effective implementation of SMS and obstacles that arise in the process of registration. The method used is the juridical empirically using primary data and secondary data. Purposive sampling is done non-random sampling. While the village is the village sample Lebosari, Watercress District, Kendal. Implementation of mass self certificate in Kendal called collective self-certificate can be made at any time without being tied to a particular fiscal year, a special committee was formed by decree of the Head of BPN and performed as the implementation of land registration individually. The Village is as a facilitator and decision maker to mass land registration organizations. While the mediator between the participants with the Land Office by a non formal called Conscious Discipline of Community Land (POKMASDARTIBNAH). The fact proves that the implementation of a mass land registration organizations are very effective in order to expedite the orderly chess program in the land sector. Obstacles in the implementation of land registration can be solved thanks to massive governmental coordination undertaken by the POKMASDARTIBNAH. The conclusion of this research is the implementation of land registration mass organizations in the Village District Lebosari Kangkung Kendal has different stages compared with similar enrollment in other areas, but the results do not diminish legal certainty to land ownership.